Purge and internal exile of female primary school teachers in post-war Madrid - Ramos Zamora, Sara; Santiesteban, Andra (Historia y Memoria de la Educación, 2022)
The purge of the teaching profession represents an example of the seizure of dissident memory, of the memory that was removed from the discourse that legitimized the Franco regime, which carried out a campaign to guarantee the collective de-memorization and counter-memory, in a society devastated by war. At the same time, the New State implemented mechanisms, with varied criteria, when evaluating and finally deciding on the professional future of teachers based on their gender. Teachers were the object of sexual repression, and there is an important bibliographical production on studies addressing the purging of primary teaching in Spain. This article aims to cover a gap still present in educational historiography, which is the study of the purging process carried out in Madrid on primary school teachers, focusing on the group of teachers. The work shows how the purging process unfolded, with some peculiarities not found in other Spanish provinces. Although the general features of the procedure are similar, Madrid teachers suffered less punishment than those in other regions of the peninsula.